A Fé segundo Kant nos Limites da Razão - Délio Borges de Meneses, Ramiro (Vox Scripturae - Revista Teológica Internacional, 2011)
I define the sense of Faith that was a very important element in the making of Kant’s Philosophy of Religion. Naturally, the Prussian philosopher analyzed Christian doctrines searching for some theoretical inspiration. However, he asserts that relevant ideas of his thought or religion were in fact inspired by the reading of the Bible ideas such as those of revelation, and radical evil. Christian faith is highly appreciated by Kant among the world’s religions, because historically it has been a formidable promoter of moral education. Kant’s idealism, by the way, compels him to deny some importance to Christian theology, instead the true meaning of Christian doctrines should be determined by rational theology, the part of the philosophical reflexion dealing with religions questions. Kant’s rationalism could be corrected by greater attention to the value of Christian revelation. In conclusion, the article notes that in Kant the structure of freedom restricts the meaning of the salvific event according the Revelation.
Keywords: Kant; revelation; reason; categorical imperative; faith; faith and religion